Comparison from the strength of hamstring muscles before and after stretching and cryotherapy (Research, Society and Development, 2021)
This scientific article has as its objective to show the immediate effects caused by the stretching technique and cryotherapy in the strength of the hamstring muscles. It is made with a cross sectional study and a randomized clinical trial, with 26 individuals taking part. The individuals were split in two groups, the first one being stretching static (n=12) and the second one cryotherapy (n=14), and all volunteers were previously evaluated using the manual dynamometer isometric Hand-Held Dynamometry (HDD). Each volunteer performed three contractions and had an overall score for those, and then the individuals of both groups were submitted into the techniques destined to their group, and by the end of every procedure, were immediately re-evaluated to check on muscle strength. In the results, the population showed a homogenous response in the evaluation of the physical profile between the groups. In the application of the stretching technique, it was found significant reduction in the development of maximum isometric contraction of the hamstrings with a value of P=0,0006, differently from the group submitted into cryotherapy, which demonstrated significant alteration when compared to the initial value. Based on the data obtained by the HDD, it was possible to conclude that the short term stretching when preceded by activities of strength can cause adverse effects in its maximum development, being that cryotherapy didn’t demonstrate any alteration after its application.